Assessment of Cognitive-Driven Performance-Based Activities of Daily Living Dysfunction in Parkinson's Disease - Sulzer, Patricia; Bäumer, Alena; Hoang, Huong Giang; Becker, Sara; Lönneker, Hannah Dorothea; Grässel, Elmar; Liepelt-Scarfone, Inga (Journal of the International Neuropsychological Society, 2019)
Objectives:Parkinson's disease (PD) patients with mild cognitive impairment (PD-MCI) have an increased risk of developing dementia (PDD). As activities of daily living (ADL) impairment is mandatory for the diagnosis of PDD, assessing early signs of instrumental ADL (iADL) dysfunction, especially in PD-MCI, is essential. In PD, self- and caregiver-reported iADL performance is often confounded by motor dysfunction and mood. Objective and time-efficient performance-based measurements are needed to screen for cognitive-related iADL dysfunction. We evaluated the Erlangen Test of Activities of Daily Living in Mild Dementia and Mild Cognitive Impairment (ETAM) in PD and determined its value for characterizing a subgroup of PD-MCI patients with mild performance-based iADL impairment.Methods:Twenty-one cognitively normal PD patients (PD-NC), 24 PD-MCI patients, and 18 healthy controls (HC) were analyzed. Assessments included the ETAM, a comprehensive neuropsychological test battery, iADL, mood, and motor measurements.Results:PD-MCI patients scored significantly lower on the ETAM total score compared to PD-NC patients (p =.002), whereas HC and PD-NC patients did not statistically differ. No HC scored lower than 27 points (diagnostic cutoff for mild iADL impairment); only PD-MCI patients scored below this cutoff (29.2%) suggesting the ETAM is able to characterize a PD-MCI subgroup with early iADL impairment. PD-MCI patients below the cutoff were more impaired in the attention domain (p =.04).Conclusions:The ETAM is a potentially valuable clinical assessment, able to detect first signs of iADL dysfunction in PD-MCI. Further studies in larger cohorts are needed to evaluate the prognostic ability for predicting PDD.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Attention; Cognition; Cognitive dysfunction; Disease progression; Neuropsychological tests; Neuropsychology